Human factors application for healthcare teams in low- and medium-income countries (LMIC) to help improve patient safety and performance - Sukhpreet Singh Dubb; Rachel S. Oeppen; Tomas Svoboda; Peter A. Brennan (Journal of Oral Biology and Craniofacial Research)
Mistakes will always happen whether at work or in our personal lives. We can never completely eliminate error, but learning and disseminating lessons from these mistakes to others is essential. Human factors application for colleagues in healthcare, particularly in low- and medium-income countries (LMIC) can greatly improve patient safety and aid better team working and staff morale. Factors such as hunger, dehydration anger, and tiredness, all reduce personal performance and can raise the risk of personal error. It is vital that we understand and optimize interaction within the healthcare team members. As part of this, ineffective communication, steep hierarchy and loss of situational awareness can lead to compromised patient safety and potentially serious error.In this paper, we provide a brief overview of human factors for healthcare colleagues in LMIC. We highlight ways to reduce the chances of error and improve patient safety by recognizing and applying various human factors to our day to day practices.